2013
DOI: 10.3390/life3040524
|View full text |Cite
|
Sign up to set email alerts
|

Distance and Size Perception in Astronauts during Long-Duration Spaceflight

Abstract: Exposure to microgravity during spaceflight is known to elicit orientation illusions, errors in sensory localization, postural imbalance, changes in vestibulo-spinal and vestibulo-ocular reflexes, and space motion sickness. The objective of this experiment was to investigate whether an alteration in cognitive visual-spatial processing, such as the perception of distance and size of objects, is also taking place during prolonged exposure to microgravity. Our results show that astronauts on board the Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…If participants felt they were taller than usual, then this could cause a perceptual rescaling of the size of the room a la Alice in Wonderland. When unsure of head position in the environment, either because of an unusual posture or in microgravity (Clément et al, 2013), the depth system may get recalibrated resulting in a rescaling of the apparent size of the environment with corresponding errors in size perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If participants felt they were taller than usual, then this could cause a perceptual rescaling of the size of the room a la Alice in Wonderland. When unsure of head position in the environment, either because of an unusual posture or in microgravity (Clément et al, 2013), the depth system may get recalibrated resulting in a rescaling of the apparent size of the environment with corresponding errors in size perception.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived distances were consistently underestimated during either shortterm exposure to microgravity using parabolic flight (Clément, Lathan, & Lockerd, 2008) or long term exposure on the International Space Station (Clément, Skinner, & Lathan, 2013) leading to perceptual distortions of three dimensional objects. In the absence of a gravitational reference it seems that objects appear closer than in the presence of orientation cues.…”
Section: Introductionmentioning
confidence: 98%
“…Microgravity experiments showed that visual perception of horizontal depth is influenced by altered vestibular signals [19]. For example, perceived distances were underestimated during either short-term exposure to microgravity using parabolic flight [20] or long term exposure on the International Space Station [21] leading to perceptual distortions of three dimensional space. However, the vestibular contribution to elevation biases in visual depth perception remains under-investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Positive errors correspond to underestimations of the adjustable dimension and/or to overestimations of the reference dimension. Thus, the present experimental paradigm, similar to the one previously used by Clément et al ( , 2013, allows the quantification of the perceptive distortions of one dimension relative to another, but cannot lead to a measure of the absolute perceptive distortions for each dimension separately (see Annex 1). Table 1 shows that the error in estimating one dimension has opposite effects for the two tasks performed within a given plane.…”
Section: Discussionmentioning
confidence: 99%
“…In an analogy with previous experiments on visual perception (Clément et al , 2013, our paradigm was conceptually designed to detect distortions in the perception of a purported 3D cube. The sequential nature of haptic perception induced us, however, to focus each trial on the comparison of the relative size between two out of three possible dimensions.…”
Section: Methodsmentioning
confidence: 99%